Evaluation of third generation quaternary ammonium compounds for the sterilisation of operation theatre - Rajkumar Bharani; Sasivannan Sasivannan; I. Kannan (International Journal of Medical Research and Review, 2015)
Introduction: Sterilisation of operation theatre is the global method in the prevention of surgical wound infections. In recent years the first and second generation compounds are replaced by the third generation quaternary ammonium compounds. The efficacy of these compounds is still doubtful.Aim: An attempt has been in the present study to evaluate the third generation quaternary ammonium compounds for its efficacy in sterilisation of operation theatre.Methods: The samples were collected before and after fogging. Quaternary Ammonium Compound D-125 is used in the present study. The presence of bacteria in the indoor air was sampled by plate exposure method. The brain heart infusion agar plate was kept open for 15 minutes at the height of one metre from the level of ground. For the analysis of surface contamination, the sampling was done by swabbing the surface. The swabs were inoculated into Robertson cooked medium (HIMEDIA) and were incubated 37OC for seven days in anaerobic condition.Results: The results showed the complete removal of microorganism after 45 minutes of fogging.Conclusion: The present study has showed that the quaternary ammonium compounds are effective disinfectant and sterilisation agent in the sterilisation of operation theatre.